VALUES HIGHLIGHTING PRODUCTIVE LEARNING IN THE PROCESS OF DEBATING - Ročāne, Maija; Samuseviča, Alīda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The lack of students` motivation is quite often the reason why students have low academic abilities and achievements. However, this can be a consequence of a lack of productive learning-oriented values. The empirical findings of the survey reveal that engagement in the process of debating contributes to the ability of students to evaluate and recognize the values gained during the debates, as well as students' self-direction, which contributes to their progression and productivity in different life situations. Students` responses to the values gained in the process of debating reveal that students' ability to self-direction increases proportionally to the students` length of experience of debating, while focusing on achievements reduces. Thus the achievement of long-term goals has been highlighted in comparison with short-term goals. The aim of the publication is to find out students' opinion about the values acquired during the process of debating, revealing and characterizing the pedagogical potential of the implementation of the debate.